2022
DOI: 10.2215/cjn.03490322
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Salary and Job Satisfaction of Transplant Nephrologists in the United States

Abstract: Background and objectivesThere are no standardized benchmarks to measure productivity and compensation of transplant nephrologists in the United States, and consequently, criteria set for general nephrologists are often used.Design, setting, participants, & measurementsA web-based survey was sent to 809 nephrologists who were members of the American Society of Transplantation to gather data on measures of productivity, compensation, and job satisfaction. Factors associated with higher total compensation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
1
3
0
Order By: Relevance
“…In its 2019 Physician Compensation and Productivity Survey, SullivanCotter—a consulting group that helps health care entities establish compensation and benefit plans—reported that the median total compensations for staff physicians in the nephrology and transplant nephrology specialties were $271,800 and $273,600, respectively (9). Hence, the compensation reported by Singh et al (6) is in line with what has been previously reported. Nonetheless, local markets drive salaries more so than nationally reported data.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In its 2019 Physician Compensation and Productivity Survey, SullivanCotter—a consulting group that helps health care entities establish compensation and benefit plans—reported that the median total compensations for staff physicians in the nephrology and transplant nephrology specialties were $271,800 and $273,600, respectively (9). Hence, the compensation reported by Singh et al (6) is in line with what has been previously reported. Nonetheless, local markets drive salaries more so than nationally reported data.…”
supporting
confidence: 91%
“…The study by Singh et al (6) is the first public effort to report the clinical productivity, compensation, job satisfaction, and burnout of US transplant nephrologists. However, it has significant limitations, including the sample size, response rate, and sampling bias, with a wide range of reported values.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Although these activities are essential to multidisciplinary care and regulatory requirements, financial compensation may not be sufficient, even in developing countries. This pattern leads to low job satisfaction and threatens to sustain a sufficient KT workforce[ 80 ].…”
Section: Challenges Against Kidney Transplantation Programsmentioning
confidence: 99%